EXPERIMENTAL MODEL OF OXYGEN PERMEABILITY AND METHANOL OXIDATION WITH SILVER MEMBRANE - Cjuno H., Jesús A. (2008)
With the objective of establishing a diffusion model of oxygen permeability and methanol oxidation with silver membrane, we develop experiments under controlled conditions of flow, temperature and pressures. The results of the products analyses with physical methods, VIS, IR and GC, have shown that the oxidation happens from a proportional way to the increment of the oxygen permeability and to the respective conditions.